Seaweed-derived plant boosters: revolutionizing sustainable farming and soil health - Singh, Amanpreet; Sharma, Kartik; Chahal, Harmandeep Singh; Kaur, Harmanjot; Hasanain, Mohammad (Frontiers in Soil Science, 2025)
Seaweeds are abundant and valuable marine resources that contain a diverse range of bioactive compounds, including lipids, minerals, phytohormones, amino acids, carbohydrates, osmo-protectants, and antibacterial substances. Historically, seaweeds have been widely used in food, feed, and medicine, but their agricultural significance has gained increasing recognition in recent years. With the growing shift toward organic and sustainable farming, seaweed extracts (SEs) have been explored as biofertilizers, soil conditioners, and natural biocontrol agents. They play a crucial role in enhancing soil health, improving plant growth, and increasing resistance against pests, diseases, and abiotic stressors such as drought, salinity, and extreme temperatures. Their ability to stimulate plant defense mechanisms and promote root development makes them an eco-friendly alternative to synthetic agrochemicals. Numerous studies have demonstrated the efficacy of seaweed extracts in boosting crop productivity while minimizing environmental impact. This review highlights recent advancements in seaweed-based agricultural applications, focusing on their benefits, mechanisms of action, and potential for integration into sustainable farming practices.